Analisis Gerak Tari Sekapur Sirih Sebagai Tari Kreasi Berbasis Tradisi - Niro Mayelza; Herlinda Mansyur (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this study is to describe and analyze the Sekapur Sirih dance movement as a tradition-based creation dance. This type of research is qualitative research with descriptive methods. The informants of this study were dance creators, musicians, singers, dancers. This research uses independent instruments assisted by stationery and cameras. The data uses primary and secondary data. Data collection techniques are carried out through literature studies, observation, interviews and documentation. The stages of data analysis are data collection, data reduction, data presentation and conclusions. The results showed that Sekapur Sirih Dance as a Tradition-Based Creation Dance in terms of space, time and energy. The spatial aspect of Sekapur Sirih Dance is dance movement. Sekapur Sirih Dance uses straight lines, diagonal lines and curved lines. Straight lines have a calm impression, diagonal lines have a dynamic impression and curved lines have a soft impression. The volume contained in this dance is large and small. The dominant facing directions in this dance are front, right, left and diagonal. Levels use low, medium, and high levels. The focus of view on this dance is fore, down, and up. The time aspect of Sekapur Sirih Dance as a Tradition-Based Creation Dance is a slow tempo at the beginning of the movement, followed by medium and fast tempos. From the rhythmic element of this Sekapur Sirih Dance.